Financial Stability dan Misstatement Laporan Keuangan dengan Opportunity Fraud sebagai Variabel Moderating - Suryawan, Kadek Yoga; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p03, 2021)
The research aims to obtain empirical evidence of the influence of Financial Stability on Misstatement of Financial Statements and to determine the ability of Opportunity Fraud to moderate the influence of Financial Stability on Misstatement of Financial Statements. This research was conducted at the Indonesia Stock Exchange (IDX) which has corporate financial data, especially manufacturing companies. The method of determining the sample using a purposive sampling technique. The number of samples in this study were 308 observational data. The analysis technique used is Moderated Regression Analysis (MRA). The results showed that Financial stability had a positive effect on the misstatement of financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018 and Opportunity Fraud weakened the influence of Financial Stability on the Misstatement of Financial Statements of manufacturing companies listed on the Indonesia Stock Exchange in 2015 - 2018. Keywords: Experience; Competence; Independence; Audit Fees; Quality Audits.